(Rainforest) Mammals - Parker, Edward (Hodder Wayland London, 2003)
There are hundreds of mammals living in the rainforest. This book takes a look at the variety of mammals - their homes, food and threats. It contains 'links' boxes that highlight the relationships of rainforests and mammals to mammals around the world. It also contains panels and boxes which give facts about the forest.